Tablighi Jamaat Da'wah Movement (Study of Da'wah of the Tablighi Jamaat in Pagambiran Ampalu Nan XX . Village) Lubuak Bagaluang District, Padang City) - fajri ahmad (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2021)
This research is entitled the Tablighi Jamaat Da'wah Movement 'A Study of the Tablighi Jama'at Da'wah in Pagambiran Ampalu Nan XX Village, Lubuak Bagaluang District, Padang City' The type of research is qualitative research with da'wah and social science approaches, while the data collection techniques are observation, interviews and documentation. The research location is in the Pagambiran Ampalu Nan XX Village, Lubuak Bagalauang District, Padang City, the consideration of choosing the research location in the Pagambiran village as the headquarters of the Tablighi Jamaat at the Nurus Salam Mosque, Al Hidayah Mosque and Nurul Ikhlas Mosque.The results showed that the Tablighi Jamaat was a movement that actively carried out Islamic da'wah in the community, they were led by an amir to control the course of da'wah, the target of mad'u was the wider community regardless of religion, occupation and status, da'wah material from the Koran and hadith supported by the book of fadhilah amal and alms, the method of da'wah khuruj fi sabilillah which is carried out at the end of every month for three days while the media used in preaching is oral media such as discussions and lectures because in simple terms it only requires tongue and voice and is accepted by all circles of society.